TRANSFORMASI PERAN GURU DI MAN 4 JOMBANG: STUDI KOMPARATIF IMPLEMENTASI KURIKULUM 2013 DAN KURIKULUM MERDEKA - Dian Kusuma Wardani; Aufia Aisa; Salsabila Dinda Khumairah (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the transformation of teacher roles in the implementation of the 2013 Curriculum and the Merdeka Curriculum at MAN 4 Jombang, and to identify significant differences between the two. The shift in national curriculum policy requires teachers to adapt professionally, especially in terms of teaching approaches, assessment strategies, and student empowerment. This research employed a quantitative comparative approach using questionnaires distributed to 37 students of Class X MIA 3 and structured interviews with teachers. Validity, reliability, normality, and homogeneity tests were conducted to ensure data feasibility. The data were then analyzed using an independent sample t-test with SPSS version 22. The results show a significant difference in students’ perceptions of teacher roles between the two curricula (Sig. 0.000 < 0.05). Teachers under the Merdeka Curriculum tend to act more as facilitators and flexible learning guides, while under the 2013 Curriculum, teachers assume a more structured and directive role. These findings indicate a paradigm shift in education that demands teachers to be more adaptive, reflective, and innovative in facilitating the learning process.